Surgery for pathological T3a, T3b and lymph node positive, prostate cancer: surgical, functional and oncological outcomes. (January 2022) - Gilliland, Niall; Vennam, Sarath; Geraghty, Robert; Peacock, Julian; Crockett, Matthew; Kearley, Samantha; Oxley, Jon; Porter, Tim; Waine, Elizabeth; Aning, Jonathan; Rowe, Edward; Koupparis, Anthony
Objective: To investigate and document the surgical, functional and oncological outcomes following surgery for high-risk prostate cancer patients. Patients and methods: Patients with pathological T3a, T3b and N1 disease were extracted from our prospectively updated institutional database. Data include demographics, preoperative cancer parameters, short and long-term complications and functional results. Details of biochemical recurrence, type and oncological outcome of salvage treatments, cancer-specific and overall survival were also obtained. Results: A total of 669 patients were included; 58.9% had T3a disease, 35.9% had pT3b and 11.4% N1 disease. With a median follow-up of 66 months (8–129), overall survival was 94.3%, cancer-specific survival was 98.7% and biochemical recurrence was 45.6%. Average inpatient stay was 1 day and the overall complication rate was 9.1%; 54.2% experienced a biochemical recurrence and 90.3% went on to have one or more salvage treatments, which were varied. Significant predictors of biochemical recurrence included pathological stage, any positive margin and patient age ( P <0.005). A total of 44.9% had an immediate biochemical recurrence, with 90% receiving subsequent treatment and 20.5% having a durable response. None of the patients receiving prostate bed radiotherapy alone had a durable response. 54% had a delayed biochemical recurrence, with 63.5% receiving subsequent treatment and 44% having a durable response. Conclusions: Surgery is associated with encouraging surgical and functional outcomes, cancer-specific survival and overall survival rates in these patients. Pathological stage is a significant predictor of biochemical recurrence. The present analysis shows that long-term observation for certain patients with biochemical recurrence is appropriate and questions the effectiveness of further local salvage treatments in patients with an immediate biochemical recurrence postoperatively. Level of evidence: II